Ancient muses : archaeology and the arts - Jameson, John H.; Ehrenhard, John E.; Finn, Christine, 1959- (Tuscaloosa : University of Alabama Press, 2003)
Known widely in Europe as ""interpretive narrative archaeology, "" the practice of using creative methods to interpret and present current knowledge of the past is gaining popularity in North America. This book is the first compilation of international case studies of the various artistic methods used in this new form of education-one that makes archaeology ""come alive"" for the nonprofessional. Plays, opera, visual art, stories, poetry, performance dance, music, sculpture, digital imagery-all can effectively communicate archaeological processes and cultural values to public audience
More than just "telling the story" : interpretive narrative archaeology / John P. McCarthy -- The archaeologist as playwright / James G. Gibb -- Archaeology goes to the opera / John E. Ehrenhard and Mary R. Bullard -- Archaeology in two dimensions : the artist's perspective / Martin Pate -- Art and imagery as tools for public interpretation and education archaeology / John H. Jameson, Jr. -- Archaeology as a compelling story : the art of writing popular histories / Sharyn Kane and Richard Keeton -- Poetry and archaeology : the transformative process / Christine A. Finn -- Reflections on the design of a public art sculpture for the Westin Hotel, Palo Alto, California / David Middlebrook -- Pompeii : a site for all seasons / David G. Orr -- Evoking time and place in reconstruction and display : the case of Celtic identity and iron age art / Harold Mytum -- Art and archaeology : conflict and interpretation in a museum setting / Michael J. Williams and Margaret A. Heath -- The archaeology of music and performance in the prehistoric American southwest / Emily Donald -- Archaeology's influence on contemporary Native American art : perspectives from a monster / Lance M. Foster -- From rock art to digital image : archaeology and art in aboriginal Australia / Claire Smith and Kirsten Brett -- Archaeology in science fiction and mysteries / David G. Anderson -- RKLOG : archaeologists as fiction writers / Sarah M. Nelson -- Capturing the wanderer : nomads and archaeology in the filming of the English patient / Christine A. Finn -- Is archaeology fiction? Some thoughts about experimental ways of communicating archaeological processes to the "external world" / Nicola Laneri -- Crafting cosmos, telling Sister stories, and exploring archaeological knowledge graphically in hypertext environments / Jeanne Lopiparo and Rosemary A. Joyce.
Includes bibliographical references (pages 205-229) and index.
Print version record.
eBooks on EBSCOhost
Keywords: Archaeology -- Methodology; Archaeology -- Social aspects; Archaeology -- Philosophy; Archaeology and art; Arts and society; Public art; Public history; Archéologie -- Méthodologie.; Archéologie -- Aspect social; Archéologie -- Philosophie; Archéologie et art; Arts et société.; Art public; Histoire appliquée.; Art -- Intégration à l'architecture.; public art; SOCIAL SCIENCE -- Archaeology; Archaeology and art; Archaeology -- Methodology; Archaeology -- Philosophy; Archaeology -- Social aspects; Arts and society; Public art; Public history